Gravity Recovery of Gold - An Overview of Recent Developments - A. R. Laplante (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Gold recovery early in the flowsheet, typically from the primary grinding circuit, has seen significant advances in the past three years. Some of the advances achieved under the auspices of the AMIRA P420B Gold Processing Technology project are reviewed. The areas covered are gravity-recoverable gold (GRG) characterization, GRG behaviour in classification, gravity recovery simulation and the link between gravity recovery and cyanidation.